Boron deficiency disorders in mango (Mangifera indica): field screening, nutrient composition and amelioration by boron application - S, Saran L; Kumar, Ratan (The Indian Journal of Agricultural Sciences, 2011)
Internal necrosis (IN) is an emerging physiological anomaly of developing mango fruits due to boron deficiency which may also lead to fruit cracking (FC). Systematic field studies were conducted in six important commercial cultivars, viz ‘Dashehari’, ‘Bombay Green’, ‘Amrapali’, ‘Mallika’, ‘Lucknow Safeda’ and ‘Chausa’ to observe the severity of IN and FC incidence. The studies revealed that out of six cultivars of mango, ‘Dashehari’ was most sensitive for both the disorders, while cv. ‘Chausa’ was most tolerant under agro-climatic conditions of Doon Valley, Uttarakhand, India. The nutrient analysis of leaf and fruit of bearing branches indicated that the IN was caused due to deficiency of boron. The N content in IN affected leaf and fruit was significantly higher in comparison to the normal samples. The high leaf N in ‘Dashehari’ may be a factor behind low level of leaf B and subsequent IN disorder. Foliar sprays of boron (as disodium octaborate tetrahydrate) @ 0.10% were most effective in increasing the level of B in leaf and fruits (149.64% and 120.14%, respectively) of ‘Dashehari’ cultivar. In all, foliar application was found to be more effective than soil application in increasing yield and reducing IN and FC disorders. The IN disorder also aggravated the incidence of fruit cracking in ‘Dashehari’ cultivar.